REMOTE TEACHING DURING THE COVID-19 PANDEMIC: A VIEWPOINT ACCORDING TO PAULO FREIRE’S APPROACH - Serra, Itanna Vytoria Sousa; Lima, Josse Maria Melo; Silva, Gilberto Tadeu Reis da; Santos, Jeferson Xavier Pinheiro dos; Santana, Laiane da Silva (Cogitare Enfermagem, 2022)
Objective: to report the authors’ experiences during remote teaching in the postgraduate course in Nursing and Health, in the face of the Coronavirus pandemic, from Paulo Freire’s approach. Method: experience report based on direct observation and student participation in curricular activities, between March and June 2021, at a public university in the State of Bahia, Brazil. Data were recorded in a field diary, organized by thematic approach and analyzed through the action-reflection-action process. Results: Three dimensions were identified that revealed the scenery experienced in emergency remote teaching, aimed to ensure the qualification of higher education in health. Conclusion: The conversations during the remote classes pervaded challenges and innovations in planning and in class practice and re-signified the process of characterization of teaching practice. The prospect of offering a high quality course, stimulating the action-reflection-action process in teaching-learning became clear.